Shoulder arthropathy secondary to syringomyelia: systematic review - Anna Wawrzyniak; Przemysław Lubiatowski (EFORT Open Reviews, 2023)
Purpose: The purpose of this study was to collect and evaluate clinical and radiological evidence on shoulder neuroarthropathy (NA) in syringomyelia (SM) that may support the management and treatment of patients with this condition. Materials and methods: This systematic review is based on the analysis of reports available in PubMed, Embase, Cochrane Database of Systematic Reviews and Cochrane Central Register of Controlled Trials using the following keywords: syringomyelia, neuroarthropathy, Charcot joint and shoulder degeneration. Thirty-nine publications were found presenting case reports or case series meeting our criteria. Pooled data included a group of 65 patients and 71 shoulders with NA secondary to SM. Results: The most commonly reported symptoms were range of motion (ROM) limitation, weakness, swelling, pain and dissociated sensory loss. NA is usually monolateral and concerns only the shoulder. The average active shoulder ROM was flexion −59.2° (s.d. 37.9), internal rotation −29.8° (s.d. 22.6) and external rotation −21.1° (s.d. 23.6). Most of the patients (75%) presented with complete or nearly complete proximal humerus degeneration, while the degree of glenoid preservation varied. Fifty-two neuroarthropathic shoulders were treated conservatively with physiotherapy, anti-inflammatory medication and splinting. Eighteen patients were treated by surgical intervention. Conclusion: Shoulder NA due to SM is a devastating and progressive condition, and its course is often unpredictable. Patients with unexplained shoulder degeneration should be evaluated for SM, especially if there are additional neurological symptoms. Conservative treatment usually reduces shoulder pain without improving ROM. For select patients, shoulder arthroplasty may be a better option for restoring function.